Complexation studies of 177Lu with ethylenediaminetetramethylene phosphonic acid (EDTMP) as a bone pain palliative therapeutic radiopharmaceutical. (26th February 2016) - Sepini, Lebogang; Jansen, David; Jarvis, Neil; Zeevaart, Jan Rijn
Graphical abstract: The blood plasma simulations indicated that [Lu(EDTMP)] 5− and [Lu(EDTMP)H] 4− are the major Lu(III) complexes formed in blood plasma. Lu(III) is mainly complexed (90%) with EDTMP under simulated physiological conditions. The remaining Lu(III) is bound to low-molecular weight ligands, namely citrate and oxalate, which are present in blood plasma. Abstract: Therapeutic radiopharmaceuticals for bone pain palliation play an important role in providing quality of life for cancer patients with metastatic bone cancer. There is currently interest in using 177 Lu in many radiopharmaceuticals, since 177 Lu has favorable nuclear decay characteristics. The usefulness of 177 Lu complexed to ethylenediaminetetramethylene phosphonic acid (EDTMP) has been demonstrated in clinical trials. This study seeks to understand the in vivo chemistry of the [ 177 Lu]Lu–EDTMP complex in blood plasma. Complex formation constants of Lu(III) and Yb(III) were measured by glass electrode potentiometry at 25 °C and I  = 150 mM. The computer simulations indicated that [Lu(EDTMP)] 5− and [Lu(EDTMP)H] 4− are the major Lu(III) complexes formed in blood plasma. These results explains why [ 177 Lu]Lu–EDTMP survives competition by other blood plasma metal ions and is delivered to the metastases. A thermodynamic blood plasma simulation revealed that Lu(III) is practically quantitatively complexed to EDTMP in vivo .